Using the project management maturity model : strategic planning for project management - Kerzner, Harold (John Wiley & Sons, Inc., 2019)
Includes maturity metrics, examples, questions, and illustrations, this detailed guide offers assessment tools for organizations of all sizes to evaluate their progress in effectively integrating project management along the maturity curve. -- Edited summary from book.
Keywords: Project management.; Strategic planning.; elektronické knihy; electronic books